1983
DOI: 10.1002/hlca.19830660627
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Optically Pure 7‐Oxabicyclo [2.2.1]hept‐2‐ene Derivatives. The CD Spectrum of (+)‐(1R)‐7‐Oxabicyclo [2.2.1]hept‐5‐en‐2‐one

Abstract: Summary(-)-1-Camphanoyloxyacrylonitrile (= (-)-1 -cyanovinyl camphanate; 1) obtained from the commercially available ( -)-camphanoyl chloride and 2-0x0-propiononitrile added to furan at 20" in the presence of CU(BF,)~. 6 H 2 0 or Zn12 and gave a mixture of 2-cyano-7-oxabicyclo [2.2. IIhept-5-en-2-yl camphanates (2-5) from which isomer 5 could be obtained pure by crystallization. The latter was transformed into (+ )-( 1 R)-7-oxabicyclo [2.2.1]hept-5-en-2-one (6) in high yield and optical purity. Adducts 2-4 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…± Since the ethereal link between the conduritol-B moiety and the aglycone (4-ethyl-7-hydroxy-2H-1-benzopyran-2-one) will be generated through a S N 2 displacement, a suitably semi-protected conduritol-F intermediate was required. Among the numerous synthesis of conduritol-F that have been proposed [10], the one by Le Drian [11] has demonstrated that racemic (AE)-12 can be derived from the Diels-Alder adduct (AE)-7 of furan to 1-cyanovinyl acetate via (AE)-8 ± 11, whereas enantiomerically pure ()-12 and (À)-12 can be derived with the same ease from the Diels-Alder adducts of furan to enantiomerically pure 1-cyanovinyl esters [12]. The synthesis of (AE)-12 [11] involves the base-induced isomerization of the 7-oxabicyclo[2.2.1]heptan-2-one derivative (AE)-10 into cyclohex-2-enone (AE)-11 (91%).…”
mentioning
confidence: 99%
“…± Since the ethereal link between the conduritol-B moiety and the aglycone (4-ethyl-7-hydroxy-2H-1-benzopyran-2-one) will be generated through a S N 2 displacement, a suitably semi-protected conduritol-F intermediate was required. Among the numerous synthesis of conduritol-F that have been proposed [10], the one by Le Drian [11] has demonstrated that racemic (AE)-12 can be derived from the Diels-Alder adduct (AE)-7 of furan to 1-cyanovinyl acetate via (AE)-8 ± 11, whereas enantiomerically pure ()-12 and (À)-12 can be derived with the same ease from the Diels-Alder adducts of furan to enantiomerically pure 1-cyanovinyl esters [12]. The synthesis of (AE)-12 [11] involves the base-induced isomerization of the 7-oxabicyclo[2.2.1]heptan-2-one derivative (AE)-10 into cyclohex-2-enone (AE)-11 (91%).…”
mentioning
confidence: 99%
“…[32] Modifications of the acetate functionality are also known: in 1997, MaGee reported the incorporation of a more electron-withdrawing 2,4-dinitrobenzoate moiety (dienophile 11), providing an increase in DA reactivity of ,5-6 times (comparable reactivity with acrylonitrile (35), discussed in the section Acrylonitriles). [33] In addition, Vogel and coworkers demonstrated that by the incorporation of chiral auxiliaries, [34][35][36][37][38][39] such as in tartaric acid-derived dienophile 12, [34] enantiomerically pure ketones were accessible via this methodology.…”
Section: Masked Ketenes As Dienophiles In the Diels-alder Reaction VImentioning
confidence: 99%
“…Particularly useful is the ability to isolate the endo -carbonitrile 4 in its optically pure form. This is the minor isomer obtained from the Diels-Alder additions of furan to a-acetoxyacrylonitrile and (-)-1-cyanovinyl camphanate [4].…”
Section: Fluoropropyl-hydroxymethylidene)-~-camphorato]europium (111)mentioning
confidence: 99%
“…[9] is also reported. The 2x11,-catalyzed Diels-Alder addition [4] of furan to or-acetoxyacrylonitrile ( = 1-cyanovinyl acetate) gave a 4: 1 mixture (90 % crude) of the cxo-us. endo -carbonitriles (5)-3 and (&)-4 [9].…”
Section: Optical Resolution Of 7-0xabicyclo[22l]hept-2-enementioning
confidence: 99%
See 1 more Smart Citation